Clinical characteristics and outcomes of rivaroxaban 2.5 mg in chronic coronary syndrome: insights from the RICCS India study - Maity, Agnibha; Kar, Kingshuk; D., Sutakshee; Pandey, Purneshwar Kumar; Sonwani, Srishti; Cletus, Nigil; Sumeshraj; Kalliath, Suneesh; Gupta, Amit (International Journal of Research in Medical Sciences, 2025)
Background: The US Food and Drug Administration approved rivaroxaban 2.5 mg twice daily for the prevention of recurrent adverse cardiovascular events in patients with stable coronary heart disease and peripheral artery disease. This study aimed to understand the clinical characteristics and outcomes of Indian patients with chronic coronary syndrome (CCS) treated with rivaroxaban 2.5 mg, either as monotherapy or in combination therapy. Methods: This retrospective, non-randomized, non-comparative, multi-center study was conducted across approximately 175 sites in India. Patients of either gender, aged >18 years, diagnosed with CCS, and who received rivaroxaban 2.5 mg were included. Patient data, including demographic details, medical history, and the treatment pattern of rivaroxaban 2.5 mg, were collected from the medical records and analyzed. Results: A total of 1299 patients were included, with a median age of 62.00 years. Most patients were men (67.82%). The median systolic and diastolic blood pressures of the patients were 138.00 mmHg and 90.00 mmHg, respectively. Patients had a medical history of diabetes mellitus (41.72%), hypertension (38.95%), and cardiovascular disease (36.25%). Nearly 70% of patients received rivaroxaban 2.5 mg twice daily with low-dose aspirin (75 mg). The treatment duration was >3 months for 21.94% of patients, 1-3 months for 41.57%, and ≤1 month for 11.24%. Major bleeding events were reported in 24 patients (1.85%), while major adverse cardiovascular events occurred in 35 patients (2.69%). Conclusions: This study provides real-world insights into clinical characteristics, treatment pattern, and outcomes of rivaroxaban 2.5 mg in patients with CCS in India.